2020
DOI: 10.1101/2020.06.17.156430
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electrophysiological validation of premotor interneurons monosynaptically connected to the aCC motoneuron in theDrosophilalarval CNS

Abstract: Mapping the wired connectivity of a nervous system is a prerequisite for full understanding of function. In this respect, such endeavours can be likened to genome sequencing projects. These projects similarly produce impressive amounts of data which, whilst a technical tour-de-force, remain under-utilised without validation. Validation of neuron synaptic connectivity requires electrophysiology which has the necessary temporal and spatial resolution to map synaptic connectivity. However, this technique is not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 38 publications
2
4
0
Order By: Relevance
“…Hasegawa et al, used GFP reconstitution across synaptic partners (GRASP) to predict monosynaptic connections between A18b3 and aCC/RP2, but reconstructions performed by Zarin et al, only showed synapses between A18b3 and MN19-Ib, MN5-Ib (LO1), MN6/7-Ib (RP3), MN14-Ib (RP1), and MN30-Ib (RP4). Electrophysiology supports Zarin et al, as depolarising A18b3 does not change the membrane potential recorded in aCC ( Giachello et al, 2020 ). This highlights the importance of using the same TERPS (electrophysiology) experiments that validated the connection between A27h and aCC ( Giachello et al, 2020 ), to address controversy and validate synapses posed by TEM reconstruction(s).…”
Section: The Drosophila Larval Connectomesupporting
confidence: 67%
See 3 more Smart Citations
“…Hasegawa et al, used GFP reconstitution across synaptic partners (GRASP) to predict monosynaptic connections between A18b3 and aCC/RP2, but reconstructions performed by Zarin et al, only showed synapses between A18b3 and MN19-Ib, MN5-Ib (LO1), MN6/7-Ib (RP3), MN14-Ib (RP1), and MN30-Ib (RP4). Electrophysiology supports Zarin et al, as depolarising A18b3 does not change the membrane potential recorded in aCC ( Giachello et al, 2020 ). This highlights the importance of using the same TERPS (electrophysiology) experiments that validated the connection between A27h and aCC ( Giachello et al, 2020 ), to address controversy and validate synapses posed by TEM reconstruction(s).…”
Section: The Drosophila Larval Connectomesupporting
confidence: 67%
“…Electrophysiology supports Zarin et al, as depolarising A18b3 does not change the membrane potential recorded in aCC ( Giachello et al, 2020 ). This highlights the importance of using the same TERPS (electrophysiology) experiments that validated the connection between A27h and aCC ( Giachello et al, 2020 ), to address controversy and validate synapses posed by TEM reconstruction(s). A18b3 signals (via relevant MNs) to coactive muscle group “F2” [muscles 3, 4, 5, 9, 12, 13, 18, 19, 25, 26, and 29 ( Zarin et al, 2019 )], which is (mostly) active earlier in segmental contraction than group F3.…”
Section: The Drosophila Larval Connectomesupporting
confidence: 67%
See 2 more Smart Citations
“…Drosophila could provide an early neurophysiological characterization of the mechanisms of action of new candidate compounds with potential translational anti-seizure effects ( 25 27 , 47 , 48 ). Specific neurons whose neurotransmitter identity and connectivity are known could be patch-clamped in para bss and the effect of the drug tested ( 49 ). The contribution of inherited or de novo mutations in the etiology of epilepsy, including focal epilepsy ( 6 , 50 ), is growing.…”
Section: Discussionmentioning
confidence: 99%